Diversity and distribution of scleractinian and non-scleractinian corals at selected areas in Tioman Island, Malaysia - Khodzori, Mohd Fikri Akmal; Saad, Shahbudin; Yusof, Muhammad Hamizan (2014)
Diversity and distribution of Scleractinian and Non-scleractinian corals were investigated in Teluk Benuang, Kampung Genting, Pulau Renggis and Teluk Teduh, Tioman Island. The Coral Video Transect (CVT) method was used to capture the image of corals. The recorded videos were extracted into picture frames and later were processed using Coral Point Count with Excel extensions (CPCe) software to determine percentage coral cover. The physico-chemical parameters were also measured. A total of 44 genera belong to 16 families were recorded in the study areas. Genus of Acropora, Montipora, Favia, Favites and Porites were found dominant in all sampling stations. Tlk. Teduh and Tlk. Benuang have shown the highest number of coral genera among the study areas. The Shannon-Weiner diversity index (H’) and Evenness index (EH’) of coral genera at Tlk. Teduh and Tlk. Benuang were H’= 2.40 and EH’= 0.78, and H’= 2.33 and EH’= 0.77 respectively. The geographical, morphological and depth were the factors that influence the establishment of corals. The Chi-square analysis had shown highly significant different between genera and location (p<0.01) except for genus of Acropora, Hydnophora, Plerogyra, Cycloseris, and Ctenactis. Sedimentation rate was shown clearly relationship with coral diversity and distribution. Keywords: Scleractenian coral; non-scleractinian coral; coral diversity and distribution; CVT method, Tioman Island